1977
DOI: 10.1017/s0028688500008870
|View full text |Cite
|
Sign up to set email alerts
|

II Corinthians vi. 14–vii. 1 and Food offered to Idols

Abstract: The problems surrounding the integrity of II Corinthians vi. 14–vii. I are well known. In the first place, verses vi. 11–13 and vii. 2–4 flow together rather easily as a single piece of personal appeal. ‘My heart is opened wide toward you…In a like reciprocation, I speak as to children, you also open wide (your hearts toward me)…Make room for me.’ The parenesis of vi. 14–vii. I abruptly breaks this flow of thought. Moreover, vi. 14–vii. I is a self-contained unit, which begins with a concrete prohibition suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…12 Furthermore, all other occasions of some form of εἰδώλα in Paul (of which 16 occurrences are found in 1 Cor 13 ) refer to literal idols (Webb 1992b, p. 39). Therefore, in 2 Cor 6:16, the word probably refers to literal idols as well (Fee 1977).…”
Section: Outsiders In Generalmentioning
confidence: 99%
“…12 Furthermore, all other occasions of some form of εἰδώλα in Paul (of which 16 occurrences are found in 1 Cor 13 ) refer to literal idols (Webb 1992b, p. 39). Therefore, in 2 Cor 6:16, the word probably refers to literal idols as well (Fee 1977).…”
Section: Outsiders In Generalmentioning
confidence: 99%
“…This has been done effectively by G. D. Fee, who has shown that the function of 6:14-7:1 is to warn the Corinthians that they cannot continue to participate in banquets held in pagan temples. 29 Continued attendance at such banquets involves an exposure to idolatry and a tacit acknowledgment of other allegiances, both of which are incompatible with fidelity to the sovereign God. The passage develops Paul's instructions in 1 Corinthians 10: 14-22.…”
Section: IImentioning
confidence: 99%
“…Paul's oblique reference was sufficient to place the issue delicately, but clearly, before his readers. to demonstrate an acceptable repentance or to experience the curse sanctions of the covenant(27)(28)(29)(30).16 The bearer of this 'painful letter' was Titus, whom Paul dispatched to Corinth with the instruction to report to him at Troas as soon as the response of the congregation was known. When Paul arrived in Troas and failed to find his associate, he became so disquieted he could not remain in the city (2 Cor.…”
mentioning
confidence: 99%